A Minimally Invasive Approach Towards “Ecosystem Hacking” With Honeybees - Stefanec, Martin; Hofstadler, Daniel N.; Krajník, Tomáš; Turgut, Ali Emre; Alemdar, Hande; Lennox, Barry; Şahin, Erol; Arvin, Farshad; Schmickl, Thomas (Frontiers in Robotics and AI, 2022)
Honey bees, live in colonies of thousands of individuals, that need not only to collaborate with each other, but also to interact intensively with their ecosystem. A small group of robots operating in a honey bee colony and interacting with the queen bee, a central colony element, has the potential to change the collective behavior of the entire colony and thus also improve its interaction with the surrounding ecosystem. Such a system can be used to study and understand many elements of bee behavior within hives that have not been adequately researched. We discuss here the applicability of this technology for ecosystem protection: A novel paradigm of a minimally invasive form of conservation through ``Ecosystem Hacking''. We discuss the necessary requirements for such a technology and show experimental data on the dynamics of the natural queen's court, initial designs of biomimetic robotic surrogates of court bees, and a multi-agent model of the queen bee court system. Our model is intended to serve as an AI-enhanceable coordination software for future robotic court bee surrogates and as a hardware controller for generating nature-like behavior patterns for such a robotic ensemble. It is a first step towards a team of robots working in a bio-compatible way to study honey bees and to increase their pollination performance, thus achieving a stabilizing effect at the ecosystem level.